Quantitative trait loci associated with chemical composition of the chicken carcass - Nones, K.; Ledur, M. C.; Zanella, E. L.; Klein, C.; Pinto, L. F. B.; Moura, Ana Silvia Alves Meira Tavares [UNESP]; Ruy, D. C.; Baron, E. E.; Ambo, M.; Campos, R. L. R.; Boschiero, C. [UNESP]; Burt, D. W.; et al. (Wiley-Blackwell, 2012)
Major objectives of the poultry industry are to increase meat production and to reduce carcass fatness, mainly abdominal fat. Information on growth performance and carcass composition are important for the selection of leaner meat chickens. To enhance our understanding of the genetic architecture underlying the chemical composition of chicken carcasses, an F2 population developed from a broiler similar to X similar to layer cross was used to map quantitative trait loci (QTL) affecting protein, fat, water and ash contents in chicken carcasses. Two genetic models were applied in the QTL analysis: the line-cross and the half-sib models, both using the regression interval mapping method. Six significant and five suggestive QTL were mapped in the line-cross analysis, and four significant and six suggestive QTL were mapped in the half-sib analysis. A total of eleven QTL were mapped for fat (ether extract), five for protein, four for ash and one for water contents in the carcass using both analyses. No study to date has reported QTL for carcass chemical composition in chickens. Some QTL mapped here for carcass fat content match, as expected, QTL regions previously associated with abdominal fat in the same or in different populations, and novel QTL for protein, ash and water contents in the carcass are presented here. The results described here also reinforce the need for fine mapping and to perform multi-trait analyses to better understand the genetic architecture of these traits.
Keywords: ash; broiler; fat; protein; water